Bayesian correction of H(z) data uncertainties - Jesus, J. F. [UNESP]; Gregório, T. M. [UNESP]; Andrade-Oliveira, F. [UNESP]; Valentim, R.; Matos, C. A.O. [UNESP] (Oxford University Press (OUP), 2018)
We compile 41 H(z) data from literature and use them to constrain OΛCDM and flat ΛCDM parameters. We show that the available H(z) suffers from uncertainties overestimation and propose a Bayesian method to reduce them. As a result of this method, using H(z) only, we find, in the context of OΛCDM, H0 = 69.5 ± 2.5 kms-1 Mpc-1, Ωm = 0.242 ± 0.036, and ΩΛ = 0.68 ± 0.14. In the context of flatΛCDMmodel,we have foundH0 =70.4±1.2 kms-1 Mpc-1 and Ωm = 0.256 ± 0.014. This corresponds to an uncertainty reduction of up to ≈30 per cent when compared to the uncorrected analysis in both cases.
Keywords: Cosmological parameters; Cosmology: Observations; Dark energy; Dark matter